Statement on conversion therapy. (May 2020) - ,; Alempijevic, Djordje; Beriashvili, Rusudan; Beynon, Jonathan; Birmanns, Bettina; Brasholt, Marie; Cohen, Juliet; Duque, Maximo; Duterte, Pierre; van Es, Adriaan; Fernando, Ravindra; Fincanci, Sebnem Korur; et al.
Abstract: Conversion therapy is a set of practices that aim to change or alter an individual's sexual orientation or gender identity. It is practiced in every region of the world by health professionals, religious practitioners, and community or family members often by or with the support of the state. Conversion therapy is performed despite evidence that it is ineffective and likely to cause individuals significant or severe physical and mental pain and suffering with long-term harmful effects. The purpose of this medico-legal statement is to provide legal experts, adjudicators, health care professionals, and policy makers, among others, with an understanding of: 1) the lack of medical and scientific validity of conversion therapy; 2) the likely physical and psychological consequences of undergoing conversion therapy; and 3) whether, based on these effects, conversion therapy constitutes cruel, inhuman, or degrading treatment or torture when individuals are subjected to it forcibly or without their consent. This medico-legal statement also addresses the responsibility of states in regulating the practice, the ethical implications of offering or performing it, and the role that health professionals and medical and mental health organisations should play with regards to it. Highlights: Conversion therapy is ineffective and likely to cause significant harm. Conversion therapy constitutes cruel, inhuman, or degrading treatment and torture. States should ban conversion therapy, which constitutes child abuse and fraud. Health professionals offering conversion therapy violate professional ethics. Health associations should denounce professionals who offer conversion therapy.